(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Mint leaves are vegetables used for tea especially in the northern part of Nigerian because of their nutritional and medicinal values. Fresh mint leaves are perishable and to extend their shelf-life drying the leaves is a common practice among the people. The application of a proper drying method is essential to preserve its nutritional and medicinal values. Lack of information on the drying characteristic that could be used for the design of its dryers is a major bottleneck in its processing. This accounts for the poor colour, taste, flavour of dried mint leaves found in the market.In this study, three methods were used to dry mint leaves, sun, oven and shade drying methods. Proximate analyses were carried out on the samples dried with the three methods. Samples drying characteristics were investigated using an oven at 40, 50, 60 and 70 °C. The results show that the drying method significantly affected all the proximate compositions at 5% level. Shade drying has the highest crude protein and ash contents of 7.74% and 8.48% respectively. Carbohydrates were more (30.13%) when open sun drying was employed. Oven drying favoured lowest moisture content of 7.20%, highest crude fiber of 49.34% and highest crude fat contents of 9.22%. To dry mint leaves to equilibrium moisture content, it took 140 min for samples at a drying temperature of 40 °C, 120 min at 50 °C, 90 min at 60 °C and 70 min for 70 °C. Drying of the leaves occurred in a falling rate period.